Performance evaluation of dense-graded asphalt mixture for high-strength application - Liew, Azelia Shi En (Nanyang Technological University, 2023)
Sustaining an efficient transportation system in Singapore for a large population in a limited land area is a challenge. Cost-effective road construction is vital due to budget constraints. Road pavements typically comprise granite aggregates and pen 60/70 grade binders in Singapore. Hence, to optimize road construction, it is essential to understand how aggregate gradation affects mechanical performance in high-strength applications.